(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Working with psychodiagnostic methods is one of the main conditions of professional competence of psychologists. The methods of obtaining information on personality characteristics are among the most necessary assessment tools in psychodiagnostics. In this article, the levels of knowledge and application of methods of obtaining information about a person at the stages of professional training of students of psychology education are studied. Empirical indicators are one of the determining components in the organization of research, that a person knows enough about the methods of obtaining information about its characteristics in research, can analyze its essence and apply it in practice.